A Pragmatic Analysis of Maxim Violations in Animated Conversations on the Dhot Design Channel - Dewi, Ani; Pratiwi, Dayinta (E-Link Journal, 2025)
Maxim violation is a pragmatic phenomenon that occurs in various communication contexts, including in entertainment media such as animation. This research aims to analyze the maxims' violation in the conversation of the  Dhot Design School animation series titled “Tour Bareng Keluarga Tiffany”. This research focuses on the four maxims of cooperation proposed by Grice, namely the maxims of quantity, quality, relevance, and manner. This research uses a descriptive qualitative approach with pragmatic discourse analysis techniques. The data were obtained through transcription of conversations in the animated video and then analyzed based on the types of maxim violation. The results show that in the animated conversation, there are various maxims violations used as communication strategies. The findings show that maxim violations in animation do not always hinder communication, but often serve to create humorous effects, build characters, and enhance the appeal of the story. Thus, this study contributes to understanding how maxim violation is used in entertainment discourse to enrich verbal interaction.